PENGARUH ENVIRONMENTAL PERFORMANCE TERHADAP ECONOMIC PERFORMANCE (Studi Empiris pada Perusahaan yang terdaftar di Bursa Efek Indonesia Tahun 2014- 2016 dan megikuti Program PROPER Tahun 2014-2016) - Muhammad Nur Mufid; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2018)
ABSTRACTThepurpose of this study is to examine the correlation of environmentalperformance on economic performance in the current year and the following year.The study included the type of empirical study with data collection method that isdocumentation method. Sampling technique in this research using purposivesampling technique, with the number of samples of 46 companies that followPROPER program 2014-2016 and listed in Indonesia Stock Exchange 2014-2016. Inthis study, the results of the hypothesis states that environmental performance has aneffect on theeconomicperformance in the current year and does not affect theeconomic performance in the next year. High profile companies if theywanttoimprove their economic performance in the current year should improve theirenvironmental performance in order to gain legitimacy or recognition from thecommunity as an environmentally friendly company. Thelevel of environmentalperformance is valuable information that can be considered for the decision-makingprocess by investors as a rational investment decision.Keywords : Environmental Performance , Economic Performance , PROPER